Investors’ reaction to fund’s performance: A study on fund flow-performance relationship in Islamic equity funds - an international evidence / Maimunah Johari - Maimunah , Johari (2020)
For many Islamic fund investors, in particular, the Muslims, the aim of their investment is not solely for financial rewards. Spiritual merits accrued through the observance of the Islamic principles brought forth another form of satisfaction. The compulsion to any investment, which involves any prohibited elements and businesses as prescribed by Shari’ah law, becomes an unidentified persuasion. These were despite theories, which expound that Islamic investment is a unique category of ethical investment invites a myriad of issues of investment inefficiencies. Investors who choose to invest with Islamic funds are considered irrational as they are ignoring the profitability and performance aspects of the investment. Attempting to investigate this puzzle, this thesis presents the empirical studies on Islamic fund investors’ reaction towards a fund’s performance through the measurement of fund flow-performance relationship of Islamic equity funds (IEFs). Three countries with different levels of Islamic financial development, namely Malaysia, Saudi Arabia and, Indonesia, were chosen. Data on the relationship between the fund flow and fund’s performance over the study period of 2007-2019 allowed the study to capture how investors react to top-performing and poor-performing funds through directing money into or out of the funds. The differences in Shari’ah screening criteria and the level of Islamic financial development across these countries provided ample ground to examine the reactions of investors under different jurisdictions and markets. Specifically, by using panel data analysis of static panel on monthly unbalanced panel data, this thesis strives to achieve four objectives. The first and second objectives aim to investigate the existent of asymmetric relation in IEFs across-countries and individual country. The third objective aims to make a comparison with the conventional equity funds (CEFs). The fourth objective aims to determine the influence of Islamic 5 financial development on the sensitivity of the fund flow-performance relationship. The current study contributes to the literature by presenting several new findings. It reveals that the fund flow-performance relationship of IEFs across-countries as well as in the individual country is inconsistent with the asymmetric relationship. Instead, the results suggest that both the bottom and top performances attracted more outflows (inflows) when performances are down (up). Furthermore, when the sensitivities of fund flow to funds’ performance of IEFs were compared to the conventional counterpart, the findings found that investors of IEFs across-countries reacted to the poor-performing funds and best-performing funds in the same way as CEFs investors do. Meanwhile, in the individual country, investors of IEFs in Malaysia are more sensitive to poor-performing funds in current performance, while having either no reaction or less sensitive to poorˇperforming funds of past performance as compared to their CEFs investors. Besides, IEFs investors in Malaysia are perceived to be more sensitive to the best-performing funds' performances. For Saudi Arabia, IEFs investors are more responsive to the poorˇperforming funds and best-performing funds in past performances as compared to their CEFs investors. Whereas, IEFs investors in Indonesia are either less responsive or did not react to fund’s performances. Moreover, the current study could also conclude that both IEFs and CEFs investors respond equally to the fund’s performance. Finally, the current study further ascertains that Islamic financial system development across countries influence the IEFs investors’ decision making. Although the development of Islamic banking and Islamic funds industries across-countries does not influence investors’ sophistication, however, IEFs investors in Malaysia are found to be more sophisticated where the investors are not chasing for best-performing funds while flocking out of poor performing funds.